Human Dignity in the Counseling Perspective - Andika Fawri (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2021)
Human dignity is a human nobility that distinguishes it from other creatures on earth. The purpose of writing this article is to describe human dignity in the perspective of counseling. The method used in this writing is literature study. The data collection technique in this article is the documentation technique. The data analysis technique used is content analysis technique. Based on the results of the author's search, humans are not born in an empty state where humans are given a noble spirit by God, the proof of which is the Qur'an as in its content, humans are created in the best possible shape and perfect. Human dignity is influenced by the conditions chosen by the human being, but if it is taken from the word nobility, humans must do and become a better person.